STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PELAYANAN PENDIDIKAN - Rio Friyadi; Zulfani Sesmiarni (ADIBA : JOURNAL OF EDUCATION, 2025)
This research aims to analyse and synthesise various literatures related to improving the quality of education and the implementation of integrated quality management (TQM) in educational institutions. Using a qualitative approach through the literature review method, this research examines various sources, such as scientific journals, books, and relevant research reports, especially those published in the last ten years. The main focus of this research is to understand the factors that influence the quality of education, the basic concepts of TQM, as well as strategies for implementing quality management in educational institutions. The results of the literature analysis show that improving the quality of education is strongly influenced by factors such as suboptimal management, limited learning facilities and the quality of human resources. In addition, the implementation of TQM in education can help educational institutions to improve overall quality through a standardised and sustainable system. This study also provides practical recommendations for educational institutions to implement TQM principles to achieve better education quality.